2016
DOI: 10.5296/ijsw.v3i1.8626
|View full text |Cite
|
Sign up to set email alerts
|

Male Survivor Perceptions of Seeking Support: Hermeneutic Analysis of a Cluster Case Study

Abstract: Studies with male survivors of child sexual abuse (CSA) are limited in focus and only one study, to date, has explored survivor perceptions of sexual assault treatment services. The current study, sought to deepen the understanding of survivor experience by identifying the triggers and barriers for seeking support as well as how survivors overcome these barriers. A cluster case study design was used with three adult males. A hermeneutic analysis was utilized to identify and explore meanings from male survivor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Of the 15 studies, 6 received suboptimal scores as survivors adopted the role of consultants on isolated areas of the research and were minimally aligned with the principles of the Survivors Charter (Perôt et al, 2018). Where information was provided, studies sought consultation on ethical guidelines and protocols to improve safety (Allnock and Miller, 2013), on data collection methods to ensure relevance and acceptability (Smith et al, 2015;Bond et al, 2018), or on analysis to improve the quality and credibility (Byrne et al, 2017;Lumbasi and Barron, 2016). Engagement with survivor advisory groups at multiple stages of the research process was less frequently observed but demonstrated a more genuine form of collaboration in two instances (IICSA, 2017;Seddon et al, 2012).…”
Section: Research Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 15 studies, 6 received suboptimal scores as survivors adopted the role of consultants on isolated areas of the research and were minimally aligned with the principles of the Survivors Charter (Perôt et al, 2018). Where information was provided, studies sought consultation on ethical guidelines and protocols to improve safety (Allnock and Miller, 2013), on data collection methods to ensure relevance and acceptability (Smith et al, 2015;Bond et al, 2018), or on analysis to improve the quality and credibility (Byrne et al, 2017;Lumbasi and Barron, 2016). Engagement with survivor advisory groups at multiple stages of the research process was less frequently observed but demonstrated a more genuine form of collaboration in two instances (IICSA, 2017;Seddon et al, 2012).…”
Section: Research Activitymentioning
confidence: 99%
“…Studies that provided participating survivors with opportunities to have an active role in research activities were found to demonstrate greater alignment with some of the Survivors Charter principles. The use of flexible and survivor-led narrative approaches to data collection was found to be empowering and liberating, and amplified the voices of participating survivors (Matthew and Barron, 2015; IICSA, 2017; Seddon et al, 2012;Lumbasi and Barron, 2016;One in Four, 2015, 2019Etherington, 2005Etherington, , 2009. Additionally, data collection through survivor-led writings was found to demonstrate non-restrictive and creative forms of engagement (IICSA, 2017;One in Four, 2015, 2019Etherington, 2005).…”
Section: Research Activitymentioning
confidence: 99%
See 3 more Smart Citations